Metode Distraksi Audio dengan Media Dzikir Jaly terhadap Penurunan Kecemasan Persalinan Kala I Fase Aktif - Elita Vasra; Nurul Komariyah; Ajeng Rizky Parawansyah (Politeknik Kesehatan Tanjung Karang, 2021)
Anxiety can be experienced by someone in any situation especially in mothers who will face childbirth. Excessive anxiety in expectant mothers can also slow down cervical dilatation and further facilitate the childbirth process. Based on this, anxiety should be addressed to avoid complications during childbirth. One of the efforts in alleviating anxiety in maternity mothers is to use distraction techniques with the media of Dzikr. This study aims to know the effect of the audio distraction technique with the media of dzikr jaly on anxiety in childbirth during the active phase at Sekayu General Hospital in 2020. This research used a pre-experimental one-group pretest-posttest design. The sample was taken from the population that met the inclusion criteria, with 33 people with purposive sampling. The results of the study using t-test obtained the value of Significance 0.000 (ρ-value<0,05) means there is a meaningful difference between decreased maternity anxiety when the active phase to before and after therapy. Audio distraction technique with media of Dzikr Jaly affects the decreased anxiety in maternity mothers during the active phase of the Sekayu General Hospital.